Cultural Transference in Veeram: A Blend of a Universal Classic Play and an Indigenous Ballad of the North Malabar - Suresh, Susmitha; Venugopal, Jinju; P. P Vijayalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Veeram-Macbeth is a trilingual movie in which a universal play meets a native folklore. Scripted and directed by Jayaraj, the movie is an adaptation of Shakespeare’s Macbeth, the story of a brave Scottish general, transposed with the story of Chekavars in Puthooram Pattukal from the ballads of North Malabar (Vadakkan Pattukal). It is also a re-interpretation of the story of Chandu Chekavar from the Vadakkan Pattukal, that shares characteristic traits of Macbeth. Veeram explores the similarities in plot and themes and brings out substitutes for each character. Chandu Chekavar is the Macbeth in Vadakkan Pattukal. The stories and characters are juxtaposed to create a hybrid product. This paper looks upon the movie as a hybrid version of two classics – Macbeth and Vadakkan Pattukal, considering the cultural and filmic aspects of the production. The paper also intends to compare the situations and traits that equals Macbeth and Chandu.